Fotröta hos får : en kartläggning av hur olika länder hanterar sjukdomen - Olhav, AnnaMaria (SLU/Dept. of Clinical Sciences (until 231231), 2010)
Foot rot is a severe claw disease which occurs among sheep and goats in most parts of the world, with outbreaks in hot and humid weather. It is a contagious bacterial infection caused by Dichelobacter nodosus in association with Fusobacterium necrophorum. Foot rot has a negative impact on both animal welfare and economy.